Fashion and popular print in early modern England : depicting dress in black-letter ballads - Backhouse, Clare (I.B. Tauris, 2017)
Fashion featured in black-letter broadside ballads over a hundred years before fashion magazines appeared in England. In the seventeenth century, these single-sheet prints contained rhyming song texts and woodcut pictures, accessible to almost everyone in the country. Dress was a popular subject for ballads, as well as being a commodity with close material and cultural connections to them. This book analyses how the distinctive words and images of these ballads made meaning, both in relation to each other on the ballad sheet and in response to contemporary national events, sumptuary legislation, religious practice, economic theory, the visual arts and literature.